Case Report: A Rare Case of Autoinflammatory Phospholipase Cγ2 (PLCγ2)-Associated Antibody Deficiency and Immune Dysregulation Complicated With Gangrenous Pyoderma and Literature Review - Wu, Na; Zhang, Bingqing; Wang, Tao; Shen, Min; Zeng, Xuejun (Frontiers in Immunology, 2021)
Background Autoinflammatory phospholipase Cγ2 (PLCγ2)-associated antibody deficiency and immune dysregulation (APLAID) is a rare autoinflammatory disease caused by gain-of-function mutations in the PLCG2 gene. Here we report a rare case of APLAID patient carrying a novel heterozygous missense PLCG2 I169V mutation with gangrenous pyoderma and concomitant high serum immunoglobulin (Ig) E level. Methods The patient was diagnosed as APLAID and has been treated in our department. His phenotype and genotype were carefully documented and studied. We also conducted a comprehensive literature review on APLAID. Results A 23-year-old Chinese Han man presented with recurrent fever for 18 years and vesiculopustular rashes for 9 years, along with chronic bronchitis, leukocytosis, increased C-reactive protein, immunodeficiency and high serum IgE. Skin biopsy showed chronic inflammatory cells infiltration. A paternal heterozygous missense variant in exon 6 of the PLCG2 gene p. I169V was identified. His vesiculopustular and IgE level responded to medium dose corticosteroids. After withdrawal of steroids, he developed severe arthritis and a large deteriorating ulceration resembling pyoderma gangrenosum on the left knee. Large dose corticosteroids were suboptimal. Then he received adalimumab with satisfactory response for arthritis and skin lesion. But he got an immunodeficiency-associated lymphoproliferative disorder 2 months later. Through literature review, there were a total of 10 APLAID patients reported by six English-language publications. Vesiculopustular rashes, sinopulmonary infection and immunodeficiency were the most frequent symptoms of APLAID patients. Glucocorticoids, intravenous immunoglobulin and biologics were clinically used to treat APLAID but none of these patients had a complete recovery. Conclusions The rarity and diversity of APLAID make it difficult to be diagnosed. Our study reported the first case of APLAID with gangrenous pyoderma and concomitant high IgE carrying a novel PLCG2 mutation, which may expand the clinical phenotype and genotype of APLAID.